Impact of commuter families on adolescent development: an evaluation of the adolescent from Peninsular Malaysia - Siaw, Yan Li; Roslan, Samsilah; Abdullah, Maria Chong; Abdullah, Haslinda (Universiti Putra Malaysia Press, 2018)
This study attempted to address the question concerning the influence of commuter families on adolescent school performance using the proposed Model for Adolescent Development Among Commuter Families (MADCF). We investigated whether the adolescent problem mediates the relationship between parental readiness and adolescent school performance, and clarified the moderating effect of gender. The survey data were drawn from 434 respondents (adolescents-parents) in Malaysia. The results indicated that the adolescent externalising problem partially mediated the relationship between parental readiness and adolescent school performance. The model accounted for 21% of the variability in adolescent school performance. The moderator findings presented that gender moderates the causal effect of parental readiness and the adolescent externalising problem with respect to adolescent school performance. This study clearly shows the importance of parental readiness, and that the results are in line with the proposed mediation and moderation effects. The model proposed by this study was strongly supported.